EFFECT OF ADDING ORGANIC NUTRIENTS AND FRUIT SET REGULATOR ON CHEMICAL CHARACTERISTICS AND VEGETATIVE GROWTH OF BROAD BEAN - Al-Tabatabaee , Safa; Al-Mharib, Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
ABSTRACT A field experiment was conducted at the research station of the College of Agricultural Engineering Sciences, University of Baghdad, during the fall season of 2023–2024. The study aimed to investigate the effect of adding an organic nutrient and spraying a fruit-set regulator on the concentration of nutrient elements and vegetative growth traits of the broad bean. The experiment included two factors: the first was the type of fertilization (chemical fertilization recommendation for broad bean and different levels of the organic nutrient Karmino bloom with the addition of 25% NPK). The second factor was the application of the pod-set regulator (Oraset-x) at three concentrations (0, 0.3, 0.6 g L⁻¹). The results showed that using chemical fertilization significantly increased the concentrations of major elements (N, P, K), chlorophyll concentration, and vegetative growth traits. Additionally, applying the organic nutrient Karmino bloom at a rate of 5 L ha⁻¹ with 25% NPK resulted in significant increases in the concentrations of Zn and B. The interaction between this treatment and spraying Oraset-x at a concentration of 0.6 g L⁻¹ led to superior results in the concentrations of Zn, B, and major elements (N, P, K), as well as improved vegetative growth traits. These findings highlight the effectiveness of this combination in enhancing the nutritional content of leaves and vegetative growth traits in broad bean plants.